2018
DOI: 10.1158/1078-0432.ccr-18-0120
|View full text |Cite
|
Sign up to set email alerts
|

Improved Risk Stratification by Circulating Tumor Cell Counts in Pancreatic Cancer

Abstract: Pancreatic cancer is one of the most devastating diseases with a 5-year survival rate of 3% to 5%. Here, we investigated whether circulating tumor cells (CTC) may predict metastatic spread and survival in pancreatic cancer patients. In a prospective study, we enrolled 69 pancreatic cancer patients. In peripheral blood, CTCs were identified by MACS enrichment (anti-cytokeratin/anti-EpCam) and subsequent automated analysis after combined anti-cytokeratin/anti-CD45/DAPI staining. CTC results were correlated to es… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 40 publications
5
70
0
Order By: Relevance
“…CTC positivity in locally advanced pancreatic adenocarcinoma at any time point was an independent prognostic factor for overall survival (OS) in multivariable analysis but not for progression-free survival (PFS). A more recent study by Effenberger et al enrolled 69 patients with PDAC and identified CTCs using MACS enrichment: Here, CTC positivity was an independent risk factor of reduced PFS (HR = 4.543, P = 0.006) and OS (HR = 2.093, P = 0.028) (Effenberger et al, 2018). Studies using different platforms in PDAC patients exhibited Before the start of Tx: For a subset of cases, multiple time points after surgery The PFS of ctDNA (+) and ctDNA (À) patients (at baseline) were 7.9 and 15.2 months (P = 0.0151).…”
Section: Prognosismentioning
confidence: 93%
See 1 more Smart Citation
“…CTC positivity in locally advanced pancreatic adenocarcinoma at any time point was an independent prognostic factor for overall survival (OS) in multivariable analysis but not for progression-free survival (PFS). A more recent study by Effenberger et al enrolled 69 patients with PDAC and identified CTCs using MACS enrichment: Here, CTC positivity was an independent risk factor of reduced PFS (HR = 4.543, P = 0.006) and OS (HR = 2.093, P = 0.028) (Effenberger et al, 2018). Studies using different platforms in PDAC patients exhibited Before the start of Tx: For a subset of cases, multiple time points after surgery The PFS of ctDNA (+) and ctDNA (À) patients (at baseline) were 7.9 and 15.2 months (P = 0.0151).…”
Section: Prognosismentioning
confidence: 93%
“…A more recent study by Effenberger et al . enrolled 69 patients with PDAC and identified CTCs using MACS enrichment: Here, CTC positivity was an independent risk factor of reduced PFS (HR = 4.543, P = 0.006) and OS (HR = 2.093, P = 0.028) (Effenberger et al ., ). Studies using different platforms in PDAC patients exhibited association of CTCs with survival rates.…”
Section: Clinical Application Of Ctcs In Pdacmentioning
confidence: 97%
“…For CTC enumeration, red blood cells were lysed (RBC Lysis buffers; Thermo Fisher Scientific, Boston, MA, USA), followed by the blocking of unspecific binding sites, cell permeation, and fixation in a one-step procedure (Carcinoma Cell Enrichment and Detection Kit; Miltenyi Biotec, Bergisch Gladbach, Germany) [31,33]. After incubation, the cells were centrifuged, resuspended in 1 mL PBS solution and applied to an MS separation column attached to an OctoMACS separator (both Miltenyi Biotec, Bergisch Gladbach, Germany).…”
Section: Tumor Cell Detectionmentioning
confidence: 99%
“…These include immunoaffinity analysis (for markers including EpCAM, CD15, CD45, and CD66b); techniques for the analysis of biophysical characteristics such as size, deformability, density, and surface charge; immunofluorescence for quantification; and molecular techniques including sequence analysis for genomics and transcriptomics, mass cytometry for proteomic analysis, and targeted bisulfite sequencing for epigenetic analysis . Table highlights the potential of CTCs as biomarkers for disease progression, prognosis, and outcomes for a wide range of cancers . Figure summarizes the potential prognostic role of CTCs at various stages of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…4 Table 1 highlights the potential of CTCs as biomarkers for disease progression, prognosis, and outcomes for a wide range of cancers. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] Figure 1 summarizes the potential prognostic role of CTCs at various stages of cancer.…”
Section: Introductionmentioning
confidence: 99%